An ex vivo study on the hypercoagulability of brain cancer patients at an academic hospital by studying the morphological and viscoelastic properties of platelet-poor plasma - Bester, Janette (University of Pretoria, 2024)
Dissertation (MSc(Human Physiology))--University of Pretoria, 2024.